Dampak Efisiensi Anggaran terhadap Akurasi Pengumpulan Data Lapangan dalam Penyusunan Policy Brief Pendapatan Asli Desa (PADes) - Al Ghazali Herdiyansah; Andi Kristiawan; Mawar Mawar; Djoni Gunanto (FKIP, Universitas Palangka Raya, 2025)
This study aims to analyse the impact of budget efficiency on the quality of policy briefs within the context of managing Pendapatan Asli Desa (PADes). Using a qualitative approach involving a literature review, the study found that overly strict budget efficiency practices, particularly cuts to funding for survey fieldwork, have a negative impact on the accuracy and validity of the data required for policy briefs. Studies in several Indonesian regions show that insufficient budget allocation for data collection leads to errors in the planning and implementation of village policies. While digitalisation, such as the use of SI-PADES applications, can increase efficiency, the best results are achieved when this is accompanied by increased human resource capacity and manual data validation. The study emphasises that budget efficiency in villages must be balanced with strategic allocation for representative data collection to support evidence-based policymaking. Therefore, the study recommends fiscal efficiency, local capacity building and digital innovation as the three pillars of accountable and sustainable village financial governance.